Witnesses in South Africa, the stepchildren of the criminal justice system - Steyn, Esther (2021)
In South Africa the criminal justice system is primarily controlled by the Criminal Procedure Act1 and its application in the criminal process. The introduction of a justiciable Bill of Rights2 on 27 April 19943 ushered South Africa into a new legal and constitutional dispensation, which in tum affected the criminal justice system profoundly. In fact the criminal process has undergone an intense metamorphosis as a result of the introduction of the Bill of Rights. Witnesses and victims of crime have not escaped the impact of the Constitution on the criminal justice system. Their rightful place in the criminal justice process is the subject of this thesis